2016
DOI: 10.1021/acs.chemmater.6b02017
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced Rapid and Explosive Fragmentation of Diarylethene Crystals Having Urethane Bonding

Abstract: Crystals of diarylethenes having urethane bonding exhibited photoinduced rapid and explosive fragmentation according to the photochromic reaction. The speed of the photogenerated crystal fragments was as fast as a few meters per second. The kinetic energy was independent of size, thickness, and volume of crystals, and depended on the crystal characters, such as crystal density and strength of intermolecular hydrogen bonding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…Although there are many studies on the photochromic reaction in the crystalline phase and its applications, there is little research that focuses on the fluorescence property of diarylethenes in the solid state. In the course of study on photochromic diarylethene crystals [15][16][17][18][19][20], we have found polymorphism of a diarylethene, 1,2bis(3-methyl-5-phenyl-2-thienyl)perfluorocyclopentene (1) (Scheme 1). In n-hexane solution,…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many studies on the photochromic reaction in the crystalline phase and its applications, there is little research that focuses on the fluorescence property of diarylethenes in the solid state. In the course of study on photochromic diarylethene crystals [15][16][17][18][19][20], we have found polymorphism of a diarylethene, 1,2bis(3-methyl-5-phenyl-2-thienyl)perfluorocyclopentene (1) (Scheme 1). In n-hexane solution,…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the two closed isomers could, however, selectively be opened due to their different absorption spectra, which led to the stepwise recovery of the original shape. Locking the crystal through the introduction of supramolecular hydrogen‐bonding urethane motifs causes mechanical stress to build‐up upon UV light irradiation that results in the crystals “exploding” after accumulating enough stress . This rare phenomenon, termed the “photosalient effect,” could also be shown in the case of remarkable hollow‐shaped crystals of a DAE with the classical perfluorocyclohexene bridge, while single‐wall crystals of the same molecule experienced photoinduced bending .…”
Section: Crystalline Photoswitchable Materialsmentioning
confidence: 99%
“…For example, photoinduced helical twisting of the crystals 23 and photoinduced fragmentation of the crystals were reported. [24][25][26][27] Particularly photoinduced fragmentation and jumping of crystals were named the "photosalient effect" by Naumov. 24 Very recently complex behaviour in bending phenomena including twisting upon UV light irradiation was reported.…”
Section: Introductionmentioning
confidence: 99%